Eccentric-exercise induced inflammation attenuates the vascular responses to mental stress - Paine, Nicola J.; Ring, Christopher; Aldred, Sarah; Bosch, Jos A.; Wadley, Alex J.; Veldhuijzen van Zanten, Jet J. C. S. (Brain, behavior and immunity, 2013)
Mental stress has been identified as a trigger of myocardial infarction (MI), with inflammation and vascular responses to mental stress independently implicated as contributing factors. This study examined whether inflammation moderates the vascular responses to mental stress. Eighteen healthy male participants completed a stress task under two counter balanced conditions. In the exercise condition, a morning bout of eccentric exercise (12×5 repetitions of unilateral eccentric knee extension at 120% intensity of concentric one repetition maximum) was used to increase levels of inflammatory-responsive cytokines during an afternoon stress session scheduled 6h later. In the control condition, participants sat and relaxed for 45min, 6h prior to the afternoon stress session. Forearm blood flow, calf blood flow (measured in the leg which completed the exercise task), blood pressure, heart rate and cardiac output were assessed at rest and in response to mental stress. As expected, interleukin-6 was higher (p=.02) 6h post exercise, i.e., at the start of the stress session, as compared to the no-exercise control condition. Mental stress increased forearm blood flow, calf blood flow, blood pressure, heart rate, and cardiac output in both conditions (p’s<.001). Stress-induced calf blood flow was attenuated in the exercise condition compared to the control condition (p<.05) which was not the case for forearm blood flow. This study found that the inflammatory response to eccentric exercise attenuated the vascular responses to mental stress locally at the site of eccentric exercise-induced inflammation. The observed impairment in vascular responses to stress associated with increased levels of inflammation suggests a mechanism through which inflammation might increase the risk for MI.
Gesehen am 31.03.2022